Muscle Performance Investigated With a Novel Smart Compression Garment Based on Pressure Sensor Force Myography and Its Validation Against EMG - Belbasis, Aaron; Fuss, Franz Konstantin (Frontiers in Physiology, 2018)
Muscle activity and fatigue performance parameters were obtained and compared between both a smart compression garment and the gold-standard, a surface electromyography (EMG) system during high speed cycling in 7 participants. The smart compression garment, based on force myography, comprised of integrated pressure sensors that were sandwiched between skin and garment, located on 5 thigh muscles. The muscle activity was assessed by means of crank cycle diagrams (polar plots) that displayed the muscle activity relative to the crank cycle. The fatigue was assessed by means of the median frequency of the power spectrum of the EMG signal; the fractal dimension of the EMG signal; and the fractal dimension of the pressure signal. The smart compression garment returned performance parameters (muscle activity and fatigue) comparable to the surface EMG. The major differences were that the EMG measured the electrical activity, whereas the pressure sensor measured the mechanical activity. As such, there was a phase shift between electrical and mechanical signals, with the electrical signals preceding the mechanical counterparts in most cases. This is specifically pronounced in high speed cycling. The fatigue trend over the duration of the cycling exercise was clearly reflected in the fatigue parameters (fractal dimensions and median frequency) obtained from pressure and EMG signals. The fatigue parameter of the pressure signal (fractal dimension) showed a higher time dependency (R2 = 0.84) compared to the EMG signal. This reflects that the pressure signal puts more emphasis on the fatigue as a function of time rather than on the origin of fatigue (e.g., peripheral or central fatigue). In the light of the high-speed activity results, caution should be exerted when using data obtained from EMG for biomechanical models. In contrast to EMG data, activity data obtained from force myography are considered more appropriate and accurate as an input for biomechanical modelling as they truly reflect the mechanical muscle activity. In summary, the smart compression garment based on force myography is a valid alternative to EMG-garments and provides more accurate results at high-speed activity (avoiding the electro-mechanical delay), as well as clearly measures the progress of muscle fatigue over time.